Thromboinflammation Model-on-A-Chip by Whole Blood Microfluidics on Fixed Human Endothelium - Alexander Dupuy; Lejla Hagimola; Neil S. A. Mgaieth; Callum B. Houlahan; Renee E. Preketes-Tardiani; Paul R. Coleman; Freda H. Passam (Diagnostics, 2021)
Microfluidic devices have an established role in the study of platelets and coagulation factors in thrombosis, with potential diagnostic applications. However, few microfluidic devices have assessed the contribution of neutrophils to thrombus formation, despite increasing knowledge of neutrophils’ importance in cardiovascular thrombosis. We describe a thromboinflammation model which uses straight channels, lined with fixed human umbilical vein endothelial cells, after treatment with tumour necrosis factor-alpha. Re-calcified whole blood is perfused over the endothelium at venous and arterial shear rate. Neutrophil adhesion, platelet and fibrin thrombus formation, is measured over time by the addition of fluorescent antibodies to a whole blood sample. Fixed endothelium retains surface expression of adhesion molecules ICAM-1 and E-Selectin. Neutrophils adhere preferentially to platelet thrombi on the endothelium. Inhibitors of neutrophil adhesion and anti-inflammatory agents, such as isoquercetin, decrease neutrophil adhesion. Our model offers the advantage of the use of (1) fixed endothelium, (2) whole blood, instead of isolated neutrophils, and (3) a small amount of blood (1 mL). The characteristics of this thromboinflammation model provide the potential for further development for drug screening and point-of-care applications.